Supporting and Inhibiting Factors in the Development of Indonesian Language with the Integration of Islamic Education Values - Readi, Agus (Continuous Education: Journal of Science and Research, 2024)
This study explores the development of Indonesian language teaching materials integrated with Islamic Education (PAI) values for Grade XI students at SMA Terpadu Bustanul Arifin Bener Meriah, during the 2024-2025 academic year. The research employs a Research and Development (R&D) methodology, focusing on identifying the supporting and inhibiting factors in this integration. Key supporting factors include the availability of Indonesian language books published by Kemendiknas and strong support from Indonesian language and PAI teachers. Inhibiting factors include the absence of National Instructors (IN) for the Indonesian language subject in Situbondo Regency, limited creativity and design skills in the developed materials, inadequate IT proficiency among teachers, and time constraints. The study concludes that while the initiative shows promise, addressing these challenges is critical to ensuring the successful integration of PAI values into the curriculum. This integration aims to enhance not only linguistic skills but also the moral and spiritual development of students, aligning with the broader educational objectives of the 2013 curriculum.